Allogeneic haematopoietic cell transplant in patients with relapsed/refractory anaplastic large cell lymphoma. (19th September 2022) - Furqan, Fateeha; Ahn, Kwang W.; Chen, Yue; Kaur, Manmeet; Abutalib, Syed A.; Ahmed, Nausheen; Ahmed, Sairah; Kharfan‐Dabaja, Mohamed A.; Friedberg, Johnathan; Gregory, Tara; Hill, LaQuisa; Sterling, Cole; et al.
Summary: The prognosis of relapsed/refractory (R/R) anaplastic large cell lymphoma (ALCL) is poor. Large studies evaluating outcomes of allogeneic haematopoietic cell transplantation (allo‐HCT) in systemic R/R ALCL are not available. Using the Center for International Blood and Marrow Transplant Research (CIBMTR) database, we evaluated outcomes of 182 adults (aged ≥18 years) with R/R ALCL undergoing allo‐HCT between 2008 and 2019. Non‐relapse mortality (NRM), disease relapse/progression (REL), progression‐free survival (PFS), and overall survival (OS) were modelled using Cox proportional hazards models. The median (range) follow‐up of survivors was 62 (3–148) months. The 1‐year NRM was 18%. The 5‐year REL, PFS and OS were 32%, 41% and 56% respectively. On multivariable regression analysis African American race (hazard ratio [HR] 2.7, 95% confidence interval [CI] 1.6–4.8; p  < 0.001) and refractory disease at allo‐HCT (HR 3.2, 95% CI 1.6–6.2; p  < 0.001) were predictive of inferior OS. Similarly, African‐American race (HR 2.1, 95% CI 1.3–3.4; p  = 0.003), other minority race (HR 2.5, 95% CI 1.2–5.3; p  = 0.02) and refractory disease (HR 2.2, 95% CI 1.2–4.3; p  = 0.01) were predictive of inferior PFS. These data, demonstrate that allo‐HCT can result in durable disease control in a sizable proportion of patients with R/R ALCL. Refractory disease and racial minority status predicted inferior allo‐HCT outcomes. Whether the inferior outcomes of racial minorities with R/R ALCL after allo‐HCT are driven by differences in disease biology or disparities in post allo‐HCT care, or both, requires further investigation.